The 2010 IEEE International Conference on Information and Automation 2010
DOI: 10.1109/icinfa.2010.5512359
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of the thermal network in a space gear-bearing system

Abstract: A thermal network model of the gear-bearing system used in a certain type of space robot was built, for investigating the temperature field distribution of the system in the space environment. Based on the Fourier's law of heat conduction, the thermal impedances of the components were computed by taking the vacuum and the grease lubricant conditions into account. The temperature of the key points of the system was obtained. The finite element simulation was performed to verify the validity of the model by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Conduction is a heat transfer that takes places in all solid state parts of the circuit [11]. The conductive heat flow is described by Fourier's law of heat conduction [12]:…”
Section: A Conductionmentioning
confidence: 99%
“…Conduction is a heat transfer that takes places in all solid state parts of the circuit [11]. The conductive heat flow is described by Fourier's law of heat conduction [12]:…”
Section: A Conductionmentioning
confidence: 99%
“…The interaction between the heat source location, its intensity, and thermal expansion coefficient and machine system configuration creates complex thermal behavior. Researchers have employed various techniques, namely, finite element methods, coordinate transformation methods, neural networks, etc, in modeling the thermal characteristics [1][2][3][4]. Huang [5] used the multiple regression method to analyze the thermal deformation of a ballscrew feed drive system.…”
Section: Introductionmentioning
confidence: 99%
“…They calculated the bearing heat generation and incorporated that in ANSYS® simulation and run the analysis in Transient Thermal module. Qi et al [12] compared the calculated total thermal resistance from the mathematical model with the thermal resistance obtained from FEA of the bearing. They concluded that the thermal resistance network can be used to describe the temperature variation within the bearing.…”
Section: Introductionmentioning
confidence: 99%
“…The heat generated in the bearing is dissipated to the surrounding through modes of heat transfer. Most researchers [5,6,8,12,[15][16][17][18] designed thermal resistance network model to calculate the heat transfer through conduction and convection from the bearing. This method comprises of the network of resistances constructed among different components of the test bearing assembly.…”
Section: Introductionmentioning
confidence: 99%